2018
DOI: 10.1016/j.rmed.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lebrikizumab in adult patients with mild-to-moderate asthma not receiving inhaled corticosteroids

Abstract: This trial was registered under NCT02104674 at http://www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 16 publications
4
28
0
1
Order By: Relevance
“… 13 Further studies assessed the safety and efficacy of AZD5069, another CXCR2 antagonist, as add-on therapy in patients with severe-uncontrolled asthma. 86 Treatment with this CXCR2-selective antagonist did not reduce the frequency of severe exacerbations, thus raising major doubts about the role of CXCR2-mediated neutrophil recruitment in severe refractory asthma exacerbations and potential clinical benefits.…”
Section: Ongoing Research: Failures Promises and Unmet Needsmentioning
confidence: 98%
“… 13 Further studies assessed the safety and efficacy of AZD5069, another CXCR2 antagonist, as add-on therapy in patients with severe-uncontrolled asthma. 86 Treatment with this CXCR2-selective antagonist did not reduce the frequency of severe exacerbations, thus raising major doubts about the role of CXCR2-mediated neutrophil recruitment in severe refractory asthma exacerbations and potential clinical benefits.…”
Section: Ongoing Research: Failures Promises and Unmet Needsmentioning
confidence: 98%
“…Therefore, this genetic variant could be considered a biomarker for patients with a high likelihood of responding to this treatment. Contemporaneous with this trial, a successful phase II trial with lebrikizumab (an anti-IL-13 mAb) for treatment of asthma indicated the secreted protein periostin as a biomarker for patient selection (46); however, lebrikizumab did not show efficacy in a multicenter phase III trial (47).…”
Section: Targeting the Mediators Of The Allergic Responsementioning
confidence: 95%
“…Korenblat et al reported anaphylaxis in one patient (1 %) treated with lebrikizumab, and this reaction was attributed to a known peanut allergy [11]. In another study, lebrikizumab was well tolerated, and death and anaphylactic reactions were not reported [12].…”
Section: Lebrikizumabmentioning
confidence: 98%